A review towards Friction Stir Welding technique: working principle and process parameters - Rikko Putra Youlia; Diah Utami; Dedik Romahadi; Yang Xiawei (SINERGI, 2023)
Friction Stir Welding (FSW) is a solid-state bonding process that employes tools that are not used up and can function to connect two opposite workpieces without melting the workpiece material. The friction force has been micro-structurally tested to reformat or transform the inner state of the structure properties (atomic formation) form in metal since the kinetic energy of friction has been utilised in one of the welding techniques. Right afterwards, the studies reported that the mechanical properties also underwent a significant deformation. The aim is to determine the effect of Welding Procedure Specification (WPS) product quality. As it develops through research and applied experiments, the branch of friction-based welding discipline can be classified depending on how the friction mechanism can produce the finest solid-state joint, which is suitable to the typical property of metal and can be maximised by joint configuration. Friction Stir Welding is a friction-based welding technique that uses the stirring tool to generate friction while the workpieces are stuck on the line of the FSW joint configuration. The relevant correlations amongst process parameters and inside its respective adjustable variables are constructed to the finest principles that produced top-grades empirical reports of the weld properties. In this review, the explanation of the working principle and clarification of process parameters are presented. The cited references are selected from creditable and verifiable articles and books in the last ten years. Expectedly, it will be able to pioneer a new face of simple and understandable review articles.